Inhibition of TRPA1 channel activity in sensory neurons by the glial cell line-derived neurotrophic factor family member, artemin - Wang Shenglan; Yu Lina; Kobayashi Kimiko; Yoshida Naoki; Na Rengaowa; Yamamoto Satoshi; Noguchi Koichi; Dai Yi (SAGE Publishing, 2011)
Abstract Background The transient receptor potential (TRP) channel subtype A1 (TRPA1) is known to be expressed on sensory neurons and respond to changes in temperature, pH and local application of certain noxious chemicals such as allyl isothiocyanate (AITC). Artemin is a neuronal survival and differentiation factor and belongs to the glial cell line-derived neurotrophic factor (GDNF) family. Both TRPA1 and artemin have been reported to be involved in pathological pain initiation and maintenance. In the present study, using whole-cell patch clamp recording technique, in situ hybridization and behavioral analyses, we examined the functional interaction between TRPA1 and artemin. Results We found that 85.8 ± 1.9% of TRPA1-expressing neurons also expressed GDNF family receptor alpha 3 (GFR α3), and 87.5 ± 4.1% of GFRα3-expressing neurons were TRPA1-positive. In whole-cell patch clamp analysis, a short-term treatment of 100 ng/ml artemin significantly suppressed the AITC-induced TRPA1 currents. A concentration-response curve of AITC resulting from the effect of artemin showed that this inhibition did not change EC50 but did lower the AITC-induced maximum response. In addition, pre-treatment of artemin significantly suppressed the number of paw lifts induced by intraplantar injection of AITC, as well as the formalin-induced pain behaviors. Conclusions These findings that a short-term application of artemin inhibits the TRPA1 channel's activity and the sequential pain behaviors suggest a role of artemin in regulation of sensory neurons.